A systematically comparative study on LiNO3 and Li2SO4 aqueous electrolytes for electrochemical double-layer capacitors. (1st June 2018) - Jiang, Jianbo; Liu, Beibei; Liu, Guiyu; Qian, Dong; Yang, Chunming; Li, Junhua
Abstract: In this work, highly soluble LiNO3 was adopted as the neutrally aqueous electrolyte for active carbon (AC)-based electrochemical double-layer capacitors (EDLCs), of which the electrochemical performances were evaluated. Simultaneously, the physicochemical properties such as the ionic conductivity and viscosity of the LiNO3 aqueous solution were investigated. As compared with the most studied Li2 SO4 aqueous solution, the LiNO3 aqueous solution displays more favorable physicochemical properties and electrochemical performances as the neutral electrolytes for EDLCs. To be specific, the conductivity of the 5.0 M LiNO3 aqueous solution can reach up to 154.8 mS cm −1  at 25 °C, which is nearly two times of the maximum conductivity of 77.6 mS cm −1 for the 2.0 M Li2 SO4 aqueous solution under the identical testing conditions. Even at a concentration as high as 9.0 M, the absolute viscosity of the LiNO3 aqueous solution is only 2.4, while that of the Li2 SO4 aqueous solution achieves 3.0 at the maximum concentration of 2.5 M. Additionally, 5.0 M LiNO3 aqueous solution exhibits a wide electrochemical potential stability window from −0.9 to 0.9 V (vs. SCE) at the AC electrode, giving rise to an operating cell voltage of 1.8 V, which is comparable to that of 2.0 M Li2 SO4 aqueous solution. Further, with the 5.0 M LiNO3 aqueous solution as the electrolyte, the as-fabricated EDLC delivers an energy density up to 21.16 Wh Kg −1  at a power density of 100.09 W kg −1, which is higher than 18.43 Wh Kg −1 for the EDLC with the 2.0 M Li2 SO4 aqueous electrolyte at the identical power density. Even though the power density reaches as high as 5970 W kg −1, the energy density of the EDLC with the 5.0 M LiNO3 aqueous electrolyte can still remain at 13.1 Wh Kg −1, substantially higher than 8.71 Wh Kg −1 of the EDLC with the 2.0 M Li2 SO4 aqueous electrolyte at the same power density. Moreover, the EDLC with the 5.0 M LiNO3 aqueous electrolyte also holds good cyclic stability. After 10000 charge–discharge cycles at a current density of 1 A g −1 and a cut-off voltage of 1.8 V, the capacity retention of this EDLC retains more than 90%. These results can render an insight to explore safe, eco-friendly, inexpensive and neutrally aqueous electrolytes for supercapacitors. Graphical abstract: Image 1